Morphological characteristics and transcriptome analysis of salttolerant Trichoderma sp. responding to salt-stress conditions - Huynh Tram, Le Thi; Quoc Huy, Pham; Thi Thuy Tien, Nguyen; Thi Bich Huyen, Trinh; Thi Thuy Duong, Nguyen; Vu Bich Hanh, Dang; Kiminori, Shimizu; Xuan Dong, Nguyen (Agriculture and Natural Resources, 2025)
Importance of the work: Trichoderma spp., well known for their plant-growth-promoting characteristics and antagonistic activity against plant pathogens, present a viable solution for enhancing agricultural resilience to salinity. However, the molecular mechanisms for adaptation to salt stress in Trichoderma species are obscure. Objectives: To monitor the morphological characteristics and antagonistic capacity of Trichoderma spp. against the fungal pathogen Rhizoctonia solani in hyper-saline conditions, as well as to investigate its transcriptomic analysis. Materials and Methods: Three strains of Trichoderma (M4.1, V6.1 and CG4.2.3) were evaluated for their adaptability and their resistance to R. solani in hyper-saline conditions. Subsequently, transcriptomic analysis was applied to compare the control medium and Trichoderma asperellum V6.1, which had the highest adaptation under saline stress among the tested strains in hyper-saline conditions (3% NaCl). Results: The Trichoderma asperellum V6.1 strain not only had considerable salt tolerance but also maintained its antagonistic potential against the plant pathogenic fungus Rhizoctonia solani under saline stress. The transcriptomic analysis of the T. asperellum V6.1 strain revealed 542 differentially expressed genes involved in molecular function (121 genes), cellular component (336 genes) and biological process (46 genes). Main finding: The potential was highlighted of Trichoderma spp. as a microbial biocontrol agent in saline-affected agricultural landscapes. In addition, important insights were gained into the molecular mechanisms underlying the salt tolerance of Trichoderma asperellum V6.1.